Konsep keadilan waris dalam QS. An-Nisa' - Azizah, Firly Kamilatul (Maliki Interdisciplinary Journal, 2024)
Inheritance law is a law that regulates the transfer of hands over an inheritance, this law will regulate who is entitled to become heirs and how much each heir's share is. In QS. An-Nisa verse 11 Allah has regulated the distribution of this inheritance, which is a ratio of 2:1, one son is entitled to property equal to two daughters. This comparison is considered unfair in today's social conditions that uphold gender equality, where the justice in question is 1:1. However, when viewed from the perspective of rights and responsibilities between men and women, giving inheritance in a ratio of 2: 1 is fair, where men have responsibilities as husbands as well as children when they are married, unlike women.